FACTORS DETERMINING STUDENTS' SELF-MOTIVATION AT UNIVERSITAS RIAU - Mujiono Mujiono; Gani Haryana; Mifta Rizka (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
This research was a qualitative descriptive study aiming at revealing factors determining students’ self-motivation at Universitas Riau. Self-motivationwas a crucial element in the implementation of blended learning-based curriculum in the industrial 4.0 era. The data for this research were collected by using questionnaireswhich were distributed through google forms for all students in each faculty. They were selected as the samples in this research with a total of 515 students. The results showed that the score for ‘havingmotivation to achieve something’ was 4.21 or 84.12% which was categorized as good;the score for the commitment aspect was 4.34 or 86.70% which was categorized asgood; the score of the initiative aspect was 3.87 or 77.50% which was categorized assufficient;the score foroptimisticaspect was 4.15 or 83%, and theoverall average score was 4.14 or 82.85% which was categorized as good. Based on the 10 indicators as a determining factors for the students’ self-motivation at Universitas Riau, all of them can determine the level of achievement of the self-motivation . Sequentially, the determining factors from the highest to the lowest were needed for lectures, self-introspection, fulfilling class assignments, confidence in abilities, complacency/not giving up easily, enthusiasm for attending lectures,orientation  to success, prefering  to work on case studies, self-confidence, and managing times for study.